Analysis of the Influence of Risk Factors of Type 2 DM on Outpatients at DKT Bandar Hospital Lampung, 2020 - Feby Esmiralda; Aila Karyus; Kodrat Pramudho (Journal for Quality in Public Health, 2021)
DM is a chronic metabolic disease characterized by hyperglycemia and cause serious complications with an increasing prevalence rate. Control of risk factors that affect the incidence of DM is needed to prevent the emergence of DM and delay disease complications. The purpose of this study is to determine the risk factors that influence the incidence of type 2 diabetes outpatients at the DKT Bandar Lampung Hospital. This type of research is quantitative observational analytic with a case control approach. The population came from all patients undergoing outpatient treatment at the Internal Medicine Department of the DKT Hospital in Bandar Lampung with 44 case samples and 44 control samples. Data analysis used univariate analysis with percentages, bivariate analysis with Chi Square and multivariate analysis with multiple logistic regression. The results showed that there was a significant influence between the risk factors for age (p value 0.017), hereditary history of diabetes (p value 0.03), physical activity (p value 0.002) and obesity (p value 0.001) with the incidence of type 2 diabetes, while a history of hypertension has no effect on the incidence of type 2 diabetes mellitus (p value 0.135). Meanwhile, the most dominant variable influencing the incidence of outpatient type 2 diabetes mellitus at DKT Bandar Lampung Hospital is physical activity with OR 5.29. Maximum promotive, preventive, curative and rehabilitative efforts are needed to control risk factors for type 2 diabetes